The grand design : a novel of Dorothy Draper - Callaway, Joy (Harper Muse, 2022)
"In 1908, young Dorothy Tuckerman chafes under the bland, beige traditions of her socialite circles. Only the aristocracy's annual summer trips to the Greenbrier resort in West Virginia spark her imagination. In this naturally beautiful place, an unexpected romance with an Italian race car driver gives Dorothy a taste of the passion and adventure she wants. But her family intervenes, sentencing Dorothy to the life she'd hoped to escape.Thirty-eight years later, as World War II draws to a close, Dorothy has done everything a woman in the early twentieth century should not: she has divorced her husband - scandalous - and established America's first interior design firm - shocking. Now Dorothy returns to The Greenbrier with the assignment to restore it to something even greater than its original glory. Brimming with daring, unconventional ideas and with her beloved company's future hanging in the balance, Dorothy has one last chance to give her dreams wings or succumb to what society tells her is her inescapable fate." -- Back cover.